LA PROTECCIÓN DE LOS DERECHOS DE LAS COMUNIDADES INDÍGENAS EN LA JURISPRUDENCIA DE LA CORTE INTERAMERICANA DE DERECHOS HUMANOS (2016)
The recognition of human rights of the indigenous communities has been recently achieved. The Inter-American Court of Human Rights shows to be the regional court that has been more deeply and widely concerned with this issue handling the cases studied in this paper. In these cases the indigenous communities have claimed rights as a group. Thus, the Court has built an extensive and very protectionist doctrine, especially on the right to communal property of the ancestral lands, on the right to judicial guarantees and on the right to life.